Mosaic disturbance - Brant, Cedar, author; Beachy-Quick, Dan, advisor; Dungy, Camille, advisor; Harrow, Del, committee member; Cooperman, Matthew, committee member (Colorado State University. Libraries, 2017)
In ecology, the most resilient landscapes are ones that experience a mosaic of disturbance. This means small swaths of windfall, wildfire, and beetle kill across a landscape that create a patchwork of forest dynamics. A mosaic of disturbance increases diversity, making the land more resilient to larger, potentially-catastrophic disturbance. These poems I trace the lineages of damage in the world and in the individual. What kinds of damage open us to the world in ways that become essential to our understanding of ourselves and others? These lines often lead back to an idea of home. These poems ask how one makes a home, even as those places—physical, emotional, ecological—are always in a mosaic of damage and change. These poems accrue as an inventory, using science, myth, and symbol as organizational nets to trace patterns of disturbance and regeneration across the boundaries between self and the rest of the world.